2021
DOI: 10.3390/jpm11100993
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence and COVID-19 Using Chest CT Scan and Chest X-ray Images: Machine Learning and Deep Learning Approaches for Diagnosis and Treatment

Abstract: Objective: To report an overview and update on Artificial Intelligence (AI) and COVID-19 using chest Computed Tomography (CT) scan and chest X-ray images (CXR). Machine Learning and Deep Learning Approaches for Diagnosis and Treatment were identified. Methods: Several electronic datasets were analyzed. The search covered the years from January 2019 to June 2021. The inclusion criteria were studied evaluating the use of AI methods in COVID-19 disease reporting performance results in terms of accuracy or precisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 92 publications
3
39
0
Order By: Relevance
“…1 where three categories are included. It should be pointed out that so far plenty of researches have been carried out on identifying COVID-19 from CXR images ( Bouchareb et al, 2021 , Chandra et al, 2021 , Fan et al, 2021 , Fusco et al, 2021 , Roberts et al, 2021 , Signoroni et al, 2021 , Xu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…1 where three categories are included. It should be pointed out that so far plenty of researches have been carried out on identifying COVID-19 from CXR images ( Bouchareb et al, 2021 , Chandra et al, 2021 , Fan et al, 2021 , Fusco et al, 2021 , Roberts et al, 2021 , Signoroni et al, 2021 , Xu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…As to the “gravity assessment” of COVID-19 infection and evaluation of pulmonary parenchymal involvement, several scores have been proposed [ 62 , 63 ]. The main goal of these tools is to establish a well-defined strategy for evaluation of the airways and lungs of COVID-19 positive patients from Computed Tomography (CT) scans, including detected abnormalities [ 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ]. Their identification and the volumetric quantification may allow an easier classification in terms of gravity, extent and progression of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally worth mentioning is that the median 24 h CARE score in the present study was 9, much higher than the median value of 3 observed in the previous study of Giraudo and colleagues, performed on a population of patients with variable severity [ 11 ]. Future studies may apply artificial intelligence techniques to better discriminate different radiological severities on CXR [ 31 ].…”
Section: Discussionmentioning
confidence: 99%